Indoor air quality in educational institutions: a comparative study of VOCs and bacterial contaminants in Dubai schools - Jung, Chuloh; El Samanoudy, Gamal; Alqassimi, Nahla (Frontiers in Built Environment, 2024)
Indoor Air Quality (IAQ) research in educational institutions is crucial for ensuring the health and wellbeing of students and staff. It also contributes to academic performance, energy efficiency, regulation compliance, and cost savings. This study conducted IAQ assessments in three school buildings in Dubai to address the lack of empirical data on IAQ in educational settings. It compared IAQ standards set by the Dubai Municipality with those established by the WHO. Measurements were taken in classrooms, computer labs, and science labs, revealing that some pollutants exceeded maintenance standards, including TVOC, airborne bacteria, and noise levels. However, formaldehyde and VOCs remained within acceptable limits. Computer labs exhibited higher TVOC levels than classrooms, while science labs had even higher levels. Science labs also had higher concentrations of formaldehyde. VOC concentrations generally met WHO standards, except for elevated levels of Benzene in the science lab. TVOC, formaldehyde, airborne bacteria, CO, CO2, and other substances showed higher levels during class sessions, whereas Benzene, Toluene, Ethylbenzene, Xylene, and NO2 exhibited higher levels when classes were not in session. The study also analyzed IAQ changes over time based on building construction age. Generally, TVOC, formaldehyde (HCHO), and other substances decreased over time. However, even in buildings older than 5 years, TVOC occasionally exceeded WHO standards. These findings emphasize the significance of monitoring and maintaining proper IAQ in educational institutions to create a healthy learning environment. Policymakers, school administrators, and researchers can use these insights to develop effective strategies for enhancing IAQ and safeguarding students’ and staff’s wellbeing and academic success.